Fabrication and characterization of silk fibroin-based nanofibrous scaffolds supplemented with gelatin for corneal tissue engineering - Sahi A.K.; Varshney N.; Poddar S.; Gundu S.; Mahto S.K. (My University, 2025)
Tissue engineering is a promising approach to overcome the severe worldwide shortage of healthy donor corneas. In this work, we have developed a silk-gelatin composite scaffold using electrospinning and permeation techniques to achieve the properties comparable to cornea analog. In particular, we present the fabrication and comparative evaluation of the novel gelatin sheets consisting of silk fibroin nanofibers, which are prepared using silk fibroin (SF) (in formic acid) and SF (in aqueous) electrospun scaffolds, for its suitability as corneal stromal analogs. All the fabricated samples were treated with ethanol vapor (T) to physically crosslink the silk nanofibers. Micro/nano-scale features of the fabricated scaffolds were analyzed using scanning electron microscopy micrographs. Fourier transform infrared spectroscopy revealed characteristic peaks of polymeric functional groups and modifications upon ethanol vapor treatment. Transparency of the scaffolds was determined using UV-visible spectra. Among all the fabricated samples, the gelatin-permeated SF (in formic acid; T) scaffold showed the highest level of transparency, i.e., 77.75 ± 2.3%, which is similar to that of the native cornea (∼70%-90% [variable with age group]) with healthy acute vision. Contact angle of the samples was studied to estimate the hydrophilicity of the scaffolds. All the scaffolds except non-treated SF (in aqueous; NT) were found to be significantly stable up to 14 days when incubated in phosphate buffered saline at 37°C. Treated samples showed significantly better stability, both physically and microscopically, in comparison to nontreated samples. Proliferation and viability assays of rabbit corneal fibroblast cells (SIRC) and mouse fibroblast cells (L929 RFP) when cultured on fabricated scaffolds revealed remarkable cellular compatibility with gelatin-permeated SF (in formic acid; T) scaffolds compared to SF (in aqueous; T). Unlike other reports in the existing literature, this work presents the design and development of a nanofibrous silk-gelatin composite that exhibits acceptable transparency, cellular biocompatibility, as well as improved mechanical stability comparable to that of native cornea. Therefore, we anticipate that the fabricated novel scaffold is likely to be a good candidate for corneal tissue construct. Moreover, among the fabricated scaffolds, the outcomes depict gelatin-permeated SF (in formic acid; T) composite scaffold to be a better candidate as a corneal stromal analog that carries properties of both the silk and gelatin, i.e., optimal transparency, better stability, and enhanced cytocompatibility. © 2021 S. Karger AG, Basel. Copyright: All rights reserved.